2006
DOI: 10.1074/jbc.m513089200
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli RecQ Is a Rapid, Efficient, and Monomeric Helicase

Abstract: RecQ family helicases play a key role in chromosome maintenance. Despite extensive biochemical, biophysical, and structural studies, the mechanism by which helicase unwinds double-stranded DNA remains to be elucidated. Using a wide array of biochemical and biophysical approaches, we have previously shown that the Escherichia coli RecQ helicase functions as a monomer. In this study, we have further characterized the kinetic mechanism of the RecQ-catalyzed unwinding of duplex DNA using the fluorometric stopped-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
78
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 66 publications
12
78
3
Order By: Relevance
“…The crystal structure of a RecQ 1-516 variant, lacking the HRDC domain, indicates that the catalytic core of E. coli RecQ is monomeric in its nucleotide bound and unbound forms . Although a previous study suggested that the full-length E. coli RecQ helicase might exist as a multimer comprising at least three subunits in solution (Harmon and Kowalczykowski, 2001), more recent biochemical and biophysical studies provided evidence that this enzyme remains in a monomeric form also when bound to single-stranded DNA and when unwinding DNA, in agreement with the crystallographic results (Xu et al, 2003;Zhang et al, 2006).…”
Section: Different Oligomeric States Of Recq Helicasessupporting
confidence: 69%
“…The crystal structure of a RecQ 1-516 variant, lacking the HRDC domain, indicates that the catalytic core of E. coli RecQ is monomeric in its nucleotide bound and unbound forms . Although a previous study suggested that the full-length E. coli RecQ helicase might exist as a multimer comprising at least three subunits in solution (Harmon and Kowalczykowski, 2001), more recent biochemical and biophysical studies provided evidence that this enzyme remains in a monomeric form also when bound to single-stranded DNA and when unwinding DNA, in agreement with the crystallographic results (Xu et al, 2003;Zhang et al, 2006).…”
Section: Different Oligomeric States Of Recq Helicasessupporting
confidence: 69%
“…Stopped-flow Fluorescence Measurements-The stopped-flow assays were carried out using a Bio-Logic SFM-400 mixer with a 1.5 ϫ 1.5-mm cell (FC-15, Bio-Logic), and the Bio-Logic MOS450/AF-CD optical system was equipped with a 150-watt mercury-xenon lamp (39). Fluorescein was excited at 492 nm (2-nm slit width), and its emission was monitored at 525 nm using a high pass filter with a 20-nm bandwidth (D525/20; Chroma Technology Co.).…”
Section: Methodsmentioning
confidence: 99%
“…Paradoxically, at limiting concentrations, most RecQ helicases nonetheless efficiently unwind several kilobases of dsDNA in the course of their normal functions (9,16,(24)(25)(26), suggesting a dynamic unwinding process. Although RecQ can unwind DNA as a monomer, it also shows a functional cooperativity when unwinding DNA with an ssDNA tail (27)(28)(29). Thus, multiple monomers can bind to ssDNA to unwind long dsDNA regions.…”
mentioning
confidence: 99%